Curve-passing Analysis of Grinding Car with Independent Rotation Wheels - LI Shiping; LIU Qiling (机车电传动)
Simulation model of metro grinding car with independent rotation wheels was built with dynamic software Simpack, and wheel lateral displacement, wheel group attack angle, wheel/rail lateral force and derailment coefficient of the grinding car through 110 m small radius curve under 16 km/h speed were calculated. Curve passing performance was analyzed, and suggestions from independent rotation wheels structure were provided.